Taxonomy of Cladonia angustiloba and related species. (8th May 2018) - PINO-BODAS, Raquel; BURGAZ, Ana Rosa; AHTI, Teuvo; STENROOS, Soili
Abstract: The lichen species Cladonia angustiloba is characterized by a well-developed primary thallus and narrow squamules which show deep incisions, and the presence of usnic and fumarprotocetraric acids. Morphologically it is similar to C. foliacea and C. convoluta, from which it can be distiguished by the squamule size and morphology. Since similar characters were used to distinguish C. foliacea from C. convoluta which do not represent different lineages, it is necessary to examine the taxonomic status of C. angustiloba by means of DNA sequences. In this study, the species delimitation within the C. foliacea complex was studied by sequencing three loci, ITS rDNA, cox1 and RPB2 . The data were analyzed by means of phylogenetic and species delimitation methods (GMYC, PTP, ABGD and BPP). Our results show that none of the three species is monophyletic. Most of the species delimitation methods did not support the current species as evolutionary lineages. Only some of the BPP analyses supported C. angustiloba as a species distinct from C. foliacea and C. convoluta . However, the hypothesis that considers the C. foliacea complex as constituted by a unique species obtained the best Bayes Factor value. Therefore, C. angustiloba and C. convoluta are synonymized with C. foliacea. A new, thoroughly checked synonymy with typifications of the whole C. foliacea complex is presented. An updated survey of the world distribution data is compiled.